PENGARUH ORIENTASI KEWIRAUSAHAAN DAN INOVASI PRODUK TERHADAP KINERJA - Segara, Afifa Ayang; Novaria, Rachmawati; Mulyati, Diana Juni (Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to determine whether there is an influence between entrepreneurial orientation variables and product innovation on company performance. The method of this research is quantitative research. The population in this study is 78 employees at Amanda Brownies Surabaya who are still active working until now 2019. Using a non-probability sampling method with a purposive sampling technique with the terms Amanda Brownies employees who are in the area of Surabaya until 2019 are still actively working at Amanda Brownies . Using the solvin formula approach, the sample was 65.27 which was then rounded up by the researcher to 66 respondents. Data collection techniques using questionnaires (questionnaires). The results of the analysis of this study indicate that first, partially the value of t count> t table (4,557> 1,997) with a significant value for the value of entrepreneurial orientation is 0,000 smaller than the probability value of 0,05, or the value of 0,000 <0,05. Thus indicating that entrepreneurial orientation has a positive and significant influence on company performance. Second, partially the value of t count> t table (1.004> 1.997) with the value of Sig. for the product innovation value is 0,000 smaller than the probability value of 0.05, or the value of 0,000 <0,05. Thus indicating that product innovation has a positive and significant influence on company performance. Third, simultaneously the value of F count> F table (446,293> 3.14) with a significant value of 0,000 <0,05. From these results it can be interpreted that F count> F table, it can be concluded that entrepreneurial orientation and product innovation simultaneously have a significant effect on company performance. Keywords: Entrepreneurship Orientation, Product Innovation, and Company Performance